The Effect of Information Technology Sophistication and Technical Capability of Accounting Information System Users with Management Support as a Moderating Variable on Individual Performance - Nur Alam; Suriyanti Mangkona (International Journal of Artificial Intelligence Research, 2022)
This study aims to determine the effect of information technology sophistication and technical capabilities of users of accounting information systems with management support as a moderating variable. Data collection using primary data obtained from questionnaires using purposive sampling technique. The population was all employees of PT Hadji Kalla as many as 1,920 people, while the sample taken was 37 respondents. The results of the questionnaire have been tested for validity and reliability, and have also been tested for classical assumptions in the form of normality assumptions, multicolonierity assumptions, and heteroscedasticity assumptions. The analysis method used is multiple regression and moderate regression. The results showed that the sophistication of information technology has a positive and significant effect on individual performance, the technical ability of users of accounting information systems has a partial and simultaneous significant positive effect on individual performance, management support can simultaneously strengthen the influence of information technology sophistication on individual performance, but partially cannot strengthen the influence of information technology sophistication on individual performance, and management support can simultaneously strengthen the influence of the technical ability of users of accounting information systems on individual performance, but partially cannot strengthen the influence of the technical ability of users of accounting information systems on individual performance at PT Hadji Kalla Employees.